Wolf-ungulate interactions within the context of wolf's main prey population decline in Central Russian Upland - Anastasia O. Viricheva; Elena M. Litvinova; Maria D. Chistopolova; Andrey D. Poyarkov; Jose A. Hernandez-Blanco (Nature Conservation Research: Заповедная наука)
Canis lupus (hereinafter – wolf) is a top predator specialised on large ungulates. In a community of multiple ungulate species, carnivores may exhibit a preference for one. Due to the decreasing availability of preferred species, interactions between wolves and other ungulates can change. We conducted our research from 2014 to 2019, which included an abrupt decline in the population of the wolf's main prey, Sus scrofa, in the Kaluzhskie Zaseki State Nature Reserve, Russia. We ascertained the wolf diet (scats content analysis) and evaluated preferences using Jacobs' index. The proportion in the diet of two ungulate species, Capreolus capreolus and Alces alces, increased after the Sus scrofa population declined, but the main prey became a non-ungulate species, namely Castor fiber. Wolves did not hunt Bison bonasus, and changes in Sus scrofa populations did not affect interactions between them. The presence of this species in the wolf diet is negligible and related to scavenging. Wolves showed a strong preference for Sus scrofa after decreasing its abundance. Dynamic interactions estimated from camera-trap data, using the coefficient of sociality, partly confirmed with analysis of preferences but also depending on other factors. The coefficient of sociality showed attraction species hardly presented in the diet only in the peripheral part of the wolf home range, where ungulates more frequently encounter subadult wolves. The decreasing population of wolf's main prey influenced interactions with other ungulates to some extent since wolves increased the proportion of them in their diet to substitute Sus scrofa. In the absence of Sus scrofa, wolves tend to prefer middle- and small-sized prey.